Study of Fire Plume Behavior and Maximum Ceiling Temperature Rise in a Curved Tunnel Driven by the Coupling of Blockage Effect and Longitudinal Ventilation - Xin Zhang; Jie Li; Hao He; Xiaofeng Chen; Kai Zhu; Mingjian Yin; Ying Cao; Ke Wu (Fire)
Tunnel fires often lead to vehicles being trapped inside, causing the “blocking effect”. In this work, fire plume behavior and the maximum ceiling temperature rise in a curved tunnel with blocked vehicles under longitudinal ventilation conditions are studied numerically. The results show that, in curved tunnels, the fire plume in the quasi-stable state exhibits dynamic deflections between the concave and convex walls of the tunnel, so the location of high-temperature zones varies accordingly. The flow field structure in the near field of the blockage and the fire source is complex but can be decoupled into four characteristic sub-structures, i.e., the free shear layer, recirculation I above the vehicle blockage, recirculation II behind the downstream of the blockage, and recirculation III at the top of the tunnel. Recirculation I and II pull the fire plume upstream, while free shear layer and recirculation III pull the flame downstream. The final plume deflection direction depends on the relative strengths of these two pulling forces. As the longitudinal air velocity increases, the plume deflection direction changes from downstream to upstream of the fire source, forming the “downstream tilt—touch the ceiling above the fire source—upstream tilt” mode, resulting in the maximum ceiling temperature rise fluctuating in a decreasing-increasing-decreasing trend. Moreover, the higher the blocking ratio, the lower the critical air velocity required to induce the transition of the plume deflection directions, e.g., a critical wind speed of 3 m/s for a blockage ratio of 0.46 and a critical wind speed of 1 m/s for a blockage ratio of 0.62. Finally, a semi-empirical equation of the maximum ceiling temperature rise in curved tunnels, considering both longitudinal wind and the vehicle blocking ratio, is proposed and validated. This work highlights the multi-dimensional and non-stable plume behavior pattern in a complex tunnel fire scenario, thus providing a deeper understanding to improve the classical tunnel fire dynamic system.